Randomized study of probiotics in primary care. Issue 3 (18th June 2014) - Patel, Jasmeeta; Curry, William J.; Graybill, Marie A.; Bernard, Shaina; McDermott, Anna S.; Karpa, Kelly
Abstract Objectives Several studies have demonstrated that probiotics can be helpful in preventing antibiotic‐associated diarrhoea in hospitalized patients. However, the extent to which probiotics may benefit healthy adults taking a course of antibiotics has not been investigated in primary care. Furthermore, patient willingness to take a probiotic supplement concomitantly with antibiotics has not been explored. We aimed to conduct an exploratory study using probiotics in adults requiring an acute course of antibiotic therapy. Methods Patients prescribed antibiotics for treatment of acute infections in an outpatient family practice setting were randomized to receive either a probiotic or placebo concurrently. Patients completed adherence diaries and daily symptom checklists to assess gastrointestinal and vaginal (women) symptoms and collect information about adherence. Key findings During 179.5 h in which patients were actively recruited, 952 individuals sought care at the family practice clinic. Of these individuals, 124 were prescribed oral antibiotics; ultimately, 51 individuals met eligibility criteria, consented to participate and were randomized. Forty participants (78.4%) returned symptom diaries. No adverse effects were reported from probiotic use; however, adherence was better with the prescribed antibiotic regimen than with the study supplement (P = 0.0033). Conclusion In our pilot study, probiotics were well tolerated, although no differences were detected in any gastrointestinal or vaginal symptoms between probiotic or placebo.